Inhibition of green okra (Abelmoschus esculentus) extract against Enterococcus faecalis in tooth root canals: Penghambatan ekstrak okra hijau (Abelmoschus esculentus) terhadap Enterococcus faecalis di saluran akar gigi - Sri Lestari; Arini Tri Jayanti; Dwi Kartika Apriyono; Sulistiyani (Makassar Dental Journal, 2022)
Enterococcus faecalis is a bacterium that is often found in root canals of teeth and can survive in them even after treatment. The use of 2.5% NaOCl as a root canal irrigation material has disadvantages; toxic and irritating, so other alternatives are needed. Green okra extract contains flavonoids, alkaloids, saponins, tannins, and terpenoids which have antibacterial properties. This study aims to determine the inhibition of green okra extract against E.faecalis. It was doneexperimental laboratory research with a posttest-only control group design. The inhibition test used the disc diffusion method which consisted of 5 research groups,i.e. green okra extract with concentrations of 1.563%, 3.125%, 6.25%, 12.5%, and 2.5% NaOCl. Data were analyzed using non-pa-rametric statistical testsKruskal Wallis and Mann Whitney. The average of the inhibition zone diameter of the green okra extract concentrations were 1.563% (0 mm), 3.125% (0 mm), 6.25% (15.9 mm), 12.5% (18.03 mm), and 2.5% NaOCl (24.07 mm). The Kruskal Wallis test showed a significance value of 0.000 (p<0.05) which meant that there was a difference in the research group, followed by the Mann Whitney test which showed there were significant differences between all research groups except between green okra extract concentrations of 1.563% and 3.125%. It was concluded that green okra extract had an inhibitory effect on the growth of E.faecalis at concentrations of 6.25% and 12.5%.